External Validation of a Prediction Model for Successful External Cephalic Version - De Hundt, Marcella; Vlemmix, Floortje; Kok, Marjolein; Van Der Steeg, Jan W.; Bais, Joke M.; Mol, Ben W.; Van Der Post, Joris A. (American Journal of Perinatology, 2012)
We sought external validation of a prediction model for the probability of a successful external cephalic version (ECV). We evaluated the performance of the prediction model with calibration and discrimination. For clinical practice, we developed a score chart to calculate the probability of a successful ECV. We studied 320 women undergoing ECV, of which 117 (37%) were successful. The model underestimated the success rate by 4 to 14%. The area under the receiver operating characteristic curve was moderate (0.66; 95% confidence interval: 0.60 to 0.72), but the model was able to make good distinction between women with a higher predicted probability of a successful ECV (more than 50%) compared with women with a lower predicted probability of a successful ECV (less than 20%). Our model to predict the outcome of ECV holds in external validation. It can be used to support patient counseling and decision making for ECV in singleton term breech presentations.
Keywords: breech presentation; external cephalic version; external validation; prediction model